Collaboration Meeting with IMPACT Malaysia - Muhammad 'Arif, Mohamad (Faculty of Computing, 2021)
PEKAN, 6 July 2021 - A collaboration meeting was held virtually, between FK and IMPACT Malaysia. This collaboration proposed a program named 'Takeover program and student’s Capacity Building'.